(untitled) (Estima – Brazilian Journal of Enterostomal Therapy, 2024)
Objective: To analyze the prevalence and factors associated with infection in patients with diabetes mellitus who underwent lower extremity amputation. Method: Cross-sectional, retrospective, and analytical study carried out in a high complexity hospital in Teresina, Piauí, with 70 medical records of patients admitted from January 2015 to December 2016. Inferential analysis was performed using χ2 association tests. Pearson and Fisher’s exact, considering p<0.05 to be significant. Results: Of the 70 participants, 81.4% were over 60 years old, 57.1% were married, 41.4% had low education, 82.8% had an income of 1 to 2 minimum wages, and 52.9% were coming from the interior of Piauí. The average length of stay was 25 days. The leg was the most prevalent site of amputation (38.6%). The prevalence of infection was 74.4% and only 7.1% of patients underwent culture. Family income (p=0.032) and length of stay (p=0.014) were significantly associated with infection. Conclusion: The prevalence of infection in patients with diabetes mellitus who underwent lower extremity amputation was high, being associated with family income and length of stay, highlighting the importance of understanding these factors for implementing preventive measures.